1996
DOI: 10.1109/59.544628
|View full text |Cite
|
Sign up to set email alerts
|

The effect of automatic voltage regulation on the bifurcation evolution in power systems

Abstract: This paper discusses the relationships between types of bifurcations in power systems and their expected occurrence for voltage regulated and unregulated synchronous machines. A time-scale decomposition is performed to identify critical dynamics in the slow and fast subsystems. For singlemachine systems, the existence of an unstable limit cycle prior to Hopf bifurcation is analysed in the context of the region of attraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 12 publications
1
36
0
1
Order By: Relevance
“…Hence, the mechanism behind it is different from the modal interaction developed in Tamura and Yorino (1987), Vittal et al (1991), Lin et al (1996) and local bifurcation of stable equilibria (Dobson et al 2001). Next, multi-swing instability has been characterized as the effect of voltage control to cause an unstable limit cycle (Vournas et al 1996) and a tangled separatrix (Chu 2005), and interactions of inter-area and local plant modes (IEEE/CIGRE Joint Task Force on Stability Terms and Definitions 2004). Our mechanism is an exit across the separatrix, akin to Vournas et al (1996), Chu (2005); however, it is more complicated and is obtained for multi-machine power grids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the mechanism behind it is different from the modal interaction developed in Tamura and Yorino (1987), Vittal et al (1991), Lin et al (1996) and local bifurcation of stable equilibria (Dobson et al 2001). Next, multi-swing instability has been characterized as the effect of voltage control to cause an unstable limit cycle (Vournas et al 1996) and a tangled separatrix (Chu 2005), and interactions of inter-area and local plant modes (IEEE/CIGRE Joint Task Force on Stability Terms and Definitions 2004). Our mechanism is an exit across the separatrix, akin to Vournas et al (1996), Chu (2005); however, it is more complicated and is obtained for multi-machine power grids.…”
Section: Discussionmentioning
confidence: 99%
“…Next, multi-swing instability has been characterized as the effect of voltage control to cause an unstable limit cycle (Vournas et al 1996) and a tangled separatrix (Chu 2005), and interactions of inter-area and local plant modes (IEEE/CIGRE Joint Task Force on Stability Terms and Definitions 2004). Our mechanism is an exit across the separatrix, akin to Vournas et al (1996), Chu (2005); however, it is more complicated and is obtained for multi-machine power grids. Our result analytically gives a novel dynamical perspective of the multi-swing instability, which has been recognized as the modal interaction (IEEE/CIGRE Joint Task Force on Stability Terms and Definitions 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, three oscillatory modes have been used to explain the instability: local plant mode oscillations, inter-area mode instabilities, and multi-swing instabilities [1,3,[11][12][13][14][15][16][17][18]. In [10] the authors revealed how the three different mode oscillations interacted to destabilize a power grid and showed that the so-called collective mode of the grid was destabilized due to a perturbation from oscillatory modes with finite amplitudes determined by the grid's topology.…”
Section: Introductionmentioning
confidence: 99%
“…Improper tuning of generation control parameters may lead to Hopf bifurcation [88][89][90]. Nonlinear load may also lead to Hopf bifurcation [91].…”
Section: Voltage and Oscillatory Stability Margin Tracing Under Varyimentioning
confidence: 99%